Diagnostic and prognostic role of PAPP-A and inflammatory markers in various forms of coronary heart disease - A. O. Shevchenko; Yu. S. Slesareva; S. Al-Bustani; A. V. Bugrov; O. P. Shevchenko (Кардиоваскулярная терапия и профилактика)
Aim. To measure the blood levels of pregnancy-associated plasma protein A (PAPP-A) and inflammatory markers in patients with various forms of coronary heart disease (CHD); to evaluate their diagnostic and prognostic role. Material and methods. The study included 75 patients with unstable angina (UA), acute myocardial infarction (AIM), and stable angina. The concentrations of PAPP-A, vascular adhesion molecule (sVCAM-1) and interleukin-6 (IL-6) were measured by immuno-enzyme method; the levels of C-reactive protein (CRP) and fibrinogen were measured by latex-enhanced micro-plate immuno-turbidimetry method. The follow-up period lasted for two years. Results. A significant elevation of PAPP-A, CRP, IL-6, and sVCAM1 levels was observed in UA and AMI patients. The level of PAPP-A was significantly higher in UA participants than in those with AMI, and demonstrated the highest sensitivity and specificity in UA diagnostics. Conclusion. PAPP-A could be used as a marker of acute coronary syndrome. Its elevated levels (>10mIU/l) predict adverse outcomes in CHD patients.